ANALISIS KENAIKAN PENGHASILAN TIDAK KENA PAJAK (PTKP) TERHADAP PENERIMAAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA AMBON - LATUAMURY, SHERLIE EVABIONI (ISAS, 2022)
This study aims to determine the contribution value of the increase in non-taxable income (PTKP) to tax revenues at the Pratama Tax Service Office ( KPP Pratama Ambon) for the period 2016 to 2020. The research method used in this research is the contribution method. The data collection technique used by the researcher is direct interviews with the object under study, field observations and literature. The type of data used is quantitative data while the data sources come from primary data and secondary data.The results of the study using the contribution method showed that the contribution of thr increase in non-taxable income (PTKP) to tax revenues at tge Pratama Tax Service Office ( KPP Pratama Ambon) for the 2016 period was 24 percent, in 2017 it was 22 percent. In 2018 it was equal to 21 percent, in 2019 it is 21 percent and in 2020 it is 17 percent. Keywords : non- taxable income (PTKP), contributions, tax receipts.